Mobile instant messaging and postmillennial consumer behavior: opportunities for retail marketing (National Administration Journal, 2022)
This paper aims to examine the influence of the use of mobile instant messaging (MIM) on Post-Millennial consumer behavior in retail companies. A non-experimental quantitative research design with correlational-causal scope was conducted, for the empirical analysis used the structural equation models (PLS -SEM). As main results of the study, it was identified that marketing communications through the MIM influence satisfaction, and that these communications, the influence of other consumers and satisfaction affect the loyalty of the Post-Millennial consumer, with new evidences of the use of mobile instant messaging in marketing, retail companies can guide their strategic actions.
Keywords: Consumer satisfaction; customer loyalty; mobile marketing; retail marketing